Association between respiratory viruses and asthma in children and adolescents: a scoping review (Research, Society and Development, 2022)
Asthma is a chronic inflammatory disease that affects the airways and causes symptoms such as dyspnea, wheezing and coughing. It estimated that there are about 339 million people living with asthma in the world and that the influence of microorganisms considered a risk factor for the onset of asthma in childhood. Therefore, this review aimed to analyze the relationship between exposure to respiratory viruses and the occurrence of asthma in children and adolescents. Were searches performed in the Pubmed and Science Direct databases for articles in English using the respiratory virus AND (children OR adolescence) AND (wheezing OR asthma) search strategy. Of the 2,717 articles found, only 17 were included in the review based on the considered inclusion and exclusion criteria. The results showed that Rhinovirus and Respiratory Syncytial Virus were the most prevalent in the articles found. Additionally, detections were found for Adenoviruses, Coronaviruses, Enteroviruses, Bocaviruses, Influenza, Metapneumoviruses and Parainfluenza, in addition to the presence of coinfection between viruses and bacteria. The findings in this review may help in the development of public health strategies to prevent exacerbations of viral-induced respiratory diseases, given that many of the infections caused by these agents are seasonal in nature.